Class, Community and the Labour Movement: Wales and Canada, 1850-1930 - Earle, Michael (Labour / Le Travail, 1991)
The article reviews the book, "Class, Community and the Labour Movement: Wales and Canada, 1850-1930," edited by Deian R. Hopkin and Gregory S. Kealey, with an introduction by David Montgomery.
Keywords: BOOKS – Reviews; CLASS; Community & the Labour Movement: Wales & Canada 1850-1930 (Book); HOPKIN; Deian R.; KEALEY; Gregory S.; Labor movement; Nonfiction